Madness in the Cape Colony - Botha, Ryan (PINS-Psychology in Society, 2017)
[BOOK REVIEW] Swartz, Sally (2015) Homeless wanderers: Movement and mental illness in the Cape Colony in the nineteenth century. Cape Town: UCT Press. ISBN 978-1-77582-088-8 pbk. Pages xvi + 224. Scholarly texts on the history of psychiatry generally sketch a narrative of the progressive movement towards humane care for the mentally ill over time (see Shorter, 2003). For the most part, this analysis seems adequate. Advances in mental health care policy, clinical technologies and drug treatment have allowed for the better management and clinical care of those suffering with mental illnesses. Despite these advances, there are certain contemporary events that deeply disturb and undermine this narrative. In South Africa, The Life Esidemeni tragedy in Gauteng is a case in point. Between 23 March and 19 December 2016, it was reported that over 100 psychiatric patients had died as a result of the inadequate provision of mental health care services in the region.